Geographies of Socio-Economic Inequality - Maarten van Ham; David Manley; Tiit Tammaru (Institute of Labor Economics (IZA), 2022)
Over many decades, academics, policymakers and governments have been concerned with both the presence of inequalities and the impacts these can have on people when concentrated spatially in urban areas. This concern is especially related to the influence of spatial inequalities on individual outcomes in terms of health, education, work and income, and general well-being amongst other outcomes. In this commentary, we provide an overview of the literature on spatial inequalities and on contextual and neighbourhood effects. We address some of the main challenges in modelling contextual effects and provide evidence that no single study can definitively provide the answer to the question whether – and how much – spatial context effects are relevant for understanding individual outcomes. It is only when taken together that the rich body of research on spatial context effects shows convincingly that spatial context effects are relevant. The commentary ends with the presentation of the vicious circle of the segregation model and suggest some ways in which this vicious circle of spatial inequality and segregation can be broken.
Keywords: I30; J60; P46; R23; 330; spatial inequality; segregation; neighbourhood effects; spatial context effects